Heat acclimation does not modify autonomic responses to core cooling and the skin thermal comfort zone. (July 2020) - Sotiridis, Alexandros; Ciuha, Urša; Debevec, Tadej; Mekjavic, Igor B.
Abstract: Exercise heat acclimation (HA) is known to magnify the sweating response by virtue of a lower threshold as well as increased gain and maximal capacity of sweating. However, HA has been shown to potentiate the shivering response in a cold-air environment. We investigated whether HA would alter heat loss and heat production responses during water immersion. Twelve healthy male participants underwent a 10-day HA protocol comprising daily 90-min controlled-hyperthermia (target rectal temperature, Tre 38.5 °C) exercise sessions. Preceding and following HA, the participants performed a maximal exercise test in thermoneutral conditions (ambient temperature 23 °C, relative humidity 50%) and were, following exercise, immersed in 28 °C water for 60 min. Thermal comfort zone (TCZ) was also assessed with participants regulating the temperature of a water-perfused suit during heating and cooling. Baseline pre-immersion Tre was similar pre- and post-HA (pre: 38.33 ± 0.33 °C vs post: 38.12 ± 0.36 °C, p = 0.092). The Tre cooling rate was identical pre-to post-HA (−0.03 ± 0.01 °C·min −1, p = 0.31), as was the vasomotor response reflected in the forearm-fingertip temperature difference. Shivering thresholds (p = 0.43) and gains (p = 0.61) were not affected by HA. TCZ was established at similar temperatures, with the magnitude in regulated water temperature being 7.6 (16.3) °C pre-HA and 5.1 (24.7) °C post-HA (p = 0.65). The present findings suggest that heat production and heat loss responses during whole body cooling as well as the skin thermal comfort zone remained unaltered by a controlled-hyperthermia HA protocol. Highlights: The rate of Tre decrease during water immersion was not altered by heat acclimation. The shivering response (thresholds with respect to Tre and gains) was not affected either. TCZ was established between similar water temperatures pre- and post-acclimation.